Effectiveness of device for using interactive and cognitive therapy in the rehabilitation of patients with visuospatial neglect due to cerebral stroke during the post-acute rehabilitation period - Totska , A.V.; Nekhanevych , O.B.; Korota , Yu.V.; Mokhna , V.S.; Logvynenko , V.V. (Medicni Perspektivi, 2025)
Despite the successes of modern rehabilitation in acute stroke, the effectiveness of existing methods remains limited in patients with visuospatial neglect (VSN). This encourages the search for new methods of occupational therapy interventions, in particular, taking into account the available interactive devices. The aim of this study was to evaluate the impact of the interactive and cognitive rehabilitation device Myro on the state of cognitive functions, visuospatial perception, fine motor skills, gross upper limb functions and limitations of daily activity in patients with neglect due to stroke during the post-acute rehabilitation period. In the study 46 patients were included, 12 women and 34 men, aged 32 to 86 years (mean age was 62.8(12.8) years). All patients were assessed for their visuospatial perception, cognitive function, motor and sensory functions, and activity limitations at the beginning and the end of rehabilitation. In the first stage, during 2023-2024, 18 patients were included in the control group, who were assigned a standardized rehabilitation program. In the second stage, during 2024-2025, 28 patients participated in the main group, who were assigned an author's occupational therapy program using the Myro interactive and cognitive rehabilitation device. All patients received 3 hours of rehabilitation interventions per day for 14 days. The use of the program with an interactive device showed greater effectiveness in restoring gross motor functions of the upper limb, in particular 2.1 times better according to the results of the “Box and Blocks” test (p<0.05), to significantly greater dynamics according to the Barthel Index level (3.3 times, p<0.05). In addition, in the main group, signs of VSN were 27.1% less common at the end of therapy (p<0.05). However, after completing the rehabilitation course there weren’t the advantages of the author's program in terms of the effectiveness of improving cognitive function according to the Montreal Cognitive Test, functioning of the upper limb according to the Fugl-Meyer scale, as well as in terms of restoring fine motor skills of the upper limb according to the “9 pegs” test (p>0.05). Thus, the use of the interactive and cognitive rehabilitation device Myro has shown its effectiveness for the treatment of symptoms of VSN, recovery of gross motor functions and limitations of daily functioning in patients with the consequences of cerebral stroke. However, there is no convincing data on the superior effectiveness of this technique in patients with impaired fine motor skills of the upper limb and cognitive impairment compared to the standard program.